Supporting education the teaching assistant's handbook - Kearns, Karen 1955- (Cengage Learning Australia, 2016)
The new edition of Supporting Education, 2e is the perfect handbook for anyone who works with qualified teachers in a role supporting the education and development of school children. Supporting Education, 2e is written to support CHC30213 Certificate III in Education Support qualification, from the streamlined CHC Community Services Training Package. It provides teaching assistants with an overview of child development and how children learn, as well an introduction to the key learning areas for primary school students. The text also links to new online support resources and information to help.